1998
DOI: 10.1097/00001756-199808030-00044
|View full text |Cite
|
Sign up to set email alerts
|

Nociceptive neurons in the macaque anterior cingulate activate during anticipation of pain

Abstract: Since the anterior cingulate cortex (ACC) is known to be involved both in nociception and in anticipation that precedes the avoidance of aversive stimuli, the linking of these functions may be processed in the ACC. To test this hypothesis, we recorded single neuronal activities in the ACC of a macaque monkey while it was performing a pain-avoidance task and examined them with nociceptive cutaneous electric stimuli (ES). Thirty-six neurons responded in anticipation of the ES. Of these, 22 neurons were tested wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
68
1
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(77 citation statements)
references
References 4 publications
7
68
1
1
Order By: Relevance
“…This interpretation is supported by other studies indicating that the ACC contributes to pain-related learning. Several in vivo electrophysiological studies have shown that individual ACC neurons (some of them characterized as noci-responsive) can acquire responses to environmental cues that predict a painful stimulus (38)(39)(40). Moreover, lesions of area 24b in the rabbit disrupt a conditioned decrease in latency to avoid a noxious stimulus (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This interpretation is supported by other studies indicating that the ACC contributes to pain-related learning. Several in vivo electrophysiological studies have shown that individual ACC neurons (some of them characterized as noci-responsive) can acquire responses to environmental cues that predict a painful stimulus (38)(39)(40). Moreover, lesions of area 24b in the rabbit disrupt a conditioned decrease in latency to avoid a noxious stimulus (7).…”
Section: Discussionmentioning
confidence: 99%
“…Electrophysiological studies lend support to this view of ACC processing. First, neurons in the ACC respond both to noxious stimuli and cues that predict a noxious stimulus (8,13,14,(38)(39)(40). Interestingly, one study examined response properties of individual ACC neurons to both a pain-predictive cue and a noxious stimulus (39).…”
Section: Discussionmentioning
confidence: 99%
“…It is typically seen in the shoulders and carpal tunnels of those who propel themselves in wheelchairs and therefore use their shoulders as hips. 64 Lal in 1998 65 reported on shoulder joint degenerative changes in 72% of a sample of paraplegics. If the pain is due to nerve compression, electrophysiological studies as well as MR can aid in diagnosis.…”
Section: Secondary Overuse or Pressure Syndromesmentioning
confidence: 99%
“…The prefrontal cortex (PFC), anterior insula, and anterior cingulate cortex (ACC) are activated during the anticipation of pain, but their exact role in pain expectation remains poorly delineated (9)(10)(11)(12). Moreover, the neural mechanisms by which conscious predictions about the magnitude of pain influence the experience of pain remain poorly understood and largely unexploited in the treatment of pain.…”
mentioning
confidence: 99%